Application of Fluorescent Proteins for Functional Dissection of the Drosophila Visual System. - Smylla, T.K.; Wagner, K.; Huber, A. (International journal of molecular sciences, 2021)
The Drosophila eye has been used extensively to study numerous aspects of biological systems, for example, spatio-temporal regulation of differentiation, visual signal transduction, protein trafficking and neurodegeneration. Right from the advent of fluorescent proteins (FPs) near the end of the millennium, heterologously expressed fusion proteins comprising FPs have been applied in Drosophila vision research not only for subcellular localization of proteins but also for genetic screens and analysis of photoreceptor function. Here, we summarize applications for FPs used in the Drosophila eye as part of genetic screens, to study rhodopsin expression patterns, subcellular protein localization, membrane protein transport or as genetically encoded biosensors for Ca2+ and phospholipids in vivo. We also discuss recently developed FPs that are suitable for super-resolution or correlative light and electron microscopy (CLEM) approaches. Illustrating the possibilities provided by using FPs in Drosophila photoreceptors may aid research in other sensory or neuronal systems that have not yet been studied as well as the Drosophila eye.